2016
DOI: 10.1002/art.39636
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Analysis of the Shared Epitope Hypothesis: Binding of Arthritogenic Peptides to DRB1*04 Alleles

Abstract: Objective. The shared epitope hypothesis posits that amino acids QR/KRAA in positions 70-74 of the DRB1 chain are responsible for rheumatoid arthritis susceptibility. However, even DRB1*04 alleles containing the shared epitope vary greatly with respect to degrees of susceptibility. This study was undertaken to conduct a molecular examination of the shared epitope hypothesis by measuring binding of arthritogenic peptides to susceptibility and resistance alleles.Methods. We measured binding of native and citrull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…A common feature in RA is the presence of antibodies to citrullinated protein antigens (38), the generation of which has been associated with smoking (39). Further evidence suggests that citrullination enhances the binding affinity of some arithrogenic peptides to SE alleles (40), suggesting a pathway for interaction between smoking and HLA in RA. Our finding that citrullination increases the predicted affinity for HLA-DRB1 alleles protective in PD while decreasing the predicted affinity for HLA-DRB1 alleles predisposing to PD supports the notion that the epidemiologic association of smoking in both RA and PD is mediated by its posttranslational modification of antigens presented by HLA-DRB1 .…”
Section: Discussionmentioning
confidence: 99%
“…A common feature in RA is the presence of antibodies to citrullinated protein antigens (38), the generation of which has been associated with smoking (39). Further evidence suggests that citrullination enhances the binding affinity of some arithrogenic peptides to SE alleles (40), suggesting a pathway for interaction between smoking and HLA in RA. Our finding that citrullination increases the predicted affinity for HLA-DRB1 alleles protective in PD while decreasing the predicted affinity for HLA-DRB1 alleles predisposing to PD supports the notion that the epidemiologic association of smoking in both RA and PD is mediated by its posttranslational modification of antigens presented by HLA-DRB1 .…”
Section: Discussionmentioning
confidence: 99%
“…For the majority of the SE alleles, it has been shown that these citrullinated peptides are accommodated in a more efficient fashion than the native forms [16, 17]. To the best of our knowledge, the capacity of HLA-DQ molecules to present citrullinated ligands has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, only changes of the latter three affect the shared epitope motif. Positions 70 and 71 have a significant role in presentation of vimentin, alpha-enolase, and collagen as well as in modulating the interaction with T-cell receptors [131]. Positions 67 and 86 may also affect the binding of possible arthritogenic peptides [132].…”
Section: Contribution To Diseasementioning
confidence: 99%